FINDINGS REGARDING THE COORDINATION OF CHILDREN PRESCHOOL - Grosu Bogdan-Marius (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Analysis of the current system of physical education in the preschool shows that in most kindergartens, training activities are conducted, the subjective and objective reasons, without being systematized, at a lower organizational-methodical and lack of emotional perception. Such a situation requires a revision of the content of physical education activities for children, for the selection and application of methods and physical education most current, effective and popular. One of the imperatives of modern society in the institution in which children are educated at this age, is to increase the training process based on preparatory training disciplines: mathematics, reading and more, as well as framing extrauditory activities, which most often limits the driving functions thereof. Preschool education provides differentiated stimulation of the child to develop his intellectual, socio-emotional and psihomotric, taking into account the specific features of its age. It is known that the ontogenetic development of the child, the first to appear is movement based on its subsequently developing language and thought.